2021
DOI: 10.3389/fpsyt.2021.664499
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exercise on Sleep Quality and Insomnia in Adults: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: Study Objectives: We conducted a meta-analysis to assess the effects of different regular exercise (lasting at least 2 months on a regular basis) on self-reported and physiological sleep quality in adults. Varied exercise interventions contained traditional physical exercise (e.g., walking, cycling) and mind–body exercise characterized by gentle exercise with coordination of the body (e.g., yoga).Methods: Procedures followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 68 publications
5
39
0
2
Order By: Relevance
“…Studies on physical exercise and sleep show that participation in regular physical exercise programs has positive effects on sleep quality, mood and cognitive skills, further suggesting that high levels of exercise prevent insomnia 25,26 . Our findings also corroborate the systematic review conducted by Xie et al 27 who analyzed the effects of physical exercise on sleep quality and insomnia in adults, noting a greater risk of insomnia for those who do not exercise and a reduction in the severity of insomnia and improvements in sleep quality after its practice.…”
Section: Discussionsupporting
confidence: 91%
“…Studies on physical exercise and sleep show that participation in regular physical exercise programs has positive effects on sleep quality, mood and cognitive skills, further suggesting that high levels of exercise prevent insomnia 25,26 . Our findings also corroborate the systematic review conducted by Xie et al 27 who analyzed the effects of physical exercise on sleep quality and insomnia in adults, noting a greater risk of insomnia for those who do not exercise and a reduction in the severity of insomnia and improvements in sleep quality after its practice.…”
Section: Discussionsupporting
confidence: 91%
“…Rubio-Arias [40] et al, in a study evaluating middleaged women, found different results according to the exercise protocol applied: while there was no significant improvement in groups that performed low-intensity exercise (yoga), groups that engaged in moderate exercise (aerobic exercise) showed improvement in sleep quality. Xie et al [41], in a systematic review of 22 randomized clinical trials that included adults over 18 years of age, showed that overall, both classical exercises (walking, cycling) and mind-body exercises (yoga) improved sleep quality to the same degree.…”
Section: This Workmentioning
confidence: 99%
“…The practice of physical exercise improved subjective sleep quality in people with insomnia (symptom and disorder), but the objective improvement was observed only in individuals with insomnia symptoms 350 . There is evidence of the benefits of regular practice (duration of at least 2 months) of different types of physical exercises (physical and body-mind) in the quality of sleep and insomnia 361 . The most recent systematic review on the effects of exercise identified improvements in subjective sleep parameters, as well as decreased severity of insomnia, with a moderate power of effect 362 .…”
Section: Insomniamentioning
confidence: 99%